Association between breakfast patterns and executive function among adolescents in Shanghai, China - Wang, Xuelai; Qu, Shuangxiao; Yang, Dongling; Qi, Wenjuan; Zhang, Fengyun; Zhu, Rong; Sun, Lijing; Yan, Qiong; Qi, Yue; Yue, Guizhen; Yin, Cancan; Luo, Chunyan (Frontiers in Nutrition, 2024)
The aim of this cross-sectional study was to investigate the association between breakfast patterns and executive function among adolescents in Shanghai, China. In 2022, we randomly recruited 3012 adolescents aged 12-13 years from all administrative districts in Shanghai. Breakfast information was collected by parents using a one-day recall method. Executive function was measured using the Behavior Rating Inventory of Executive Function-Parent Version. Latent Class Analysis was performed to identify breakfast patterns based on the food groups in the Diet Quality Questionnaire for China. Breakfast patterns were classified into three categories: ‘Egg and milk foods’, ‘Grain foods’, and ‘Abundant foods’, except for adolescents who skipped breakfast. Logistic regression was used to estimate the multivariate odds ratio (ORs) and 95% confidence intervals (95% CI) for the association between breakfast patterns and potential executive dysfunction. Adolescents in the ‘Abundant foods’ class had a lower risk of executive dysfunction in terms of initiate (OR: 0.36; 95% CI: 0.17-0.76), and organization of materials (OR: 0.18; 95% CI: 0.04-0.94), compared to those who skipped breakfast. Similarly, the breakfast patterns of ‘Grain foods’ and ‘Egg and milk foods’ were associated with a lower risk of executive dysfunction, including initiate and working memory. Our findings suggest that breakfast patterns were associated with executive function. The improvement of breakfast patterns among adolescents should be a significant public health intervention.